Interaction between central volcanoes and regional tectonics along divergent plate boundaries: Askja, Iceland - Trippanera, Daniele; Ruch, Joel; Acocella, Valerio; Thordarson, Thor; Urbani, Stefano (Bulletin of Volcanology, 2017)
Activity within magmatic divergent plate boundaries (MDPB) focuses along both regional fissure swarms and central volcanoes. An ideal place to investigate their mutual relationship is the Askja central volcano in Iceland. Askja consists of three nested calderas (namely Kollur, Askja and Öskjuvatn) located within a hyaloclastite massif along the NNE-SSW trending Icelandic MDPB. We performed an extensive field-based structural analysis supported by a remote sensing study of tectonic and volcanic features of Askja’s calderas and of the eastern flank of the hyaloclastite massif. In the massif, volcano-tectonic structures trend N 10° E to N 40° E, but they vary around the Askja caldera being both parallel to the caldera rim and cross-cutting on the Western side. Structural trends around the Öskjuvatn caldera are typically rim parallel. Volcanic vents and dikes are preferentially distributed along the caldera ring faults; however, they follow the NNE-SSW regional structures when located outside the calderas. Our results highlight that the Askja volcano displays a balanced amount of regional (fissure-swarm related) and local (shallow-magma-chamber related) tectonic structures along with a mutual interaction among these. This is different from Krafla volcano (to the north of Askja) dominated by regional structures and Grímsvötn (to the South) dominated by local structures. Therefore, Askja represents an intermediate tectono-magmatic setting for volcanoes located in a slow divergent plate boundary. This is also likely in accordance with a northward increase in the spreading rate along the Icelandic MDPB. We thank the Icelandic Met Office (IMO) and the University of Iceland for providing us the possibility to use their infrastructure that allowed us to perform the field survey along with the online open access dataset. A. Gudmundsson and an anonymous reviewer provided constructive and helpful suggestions.